Adhesive Bonding for Optical Metrology Systems in Space Applications. (April 2015) - Gohlke, Martin; Schuldt, Thilo; Döringshoff, Klaus; Peters, Achim; Johann, Ulrich; Weise, Dennis; Braxmaier, Claus
Abstract: Laser based metrology systems become more and more attractive for space applications and are the core elements of planned missions such as LISA (NGO, eLISA) or NGGM where laser interferometry is used for distance measurements between satellites. The GRACE-FO mission will for the first time demonstrate a Laser Ranging Instrument (LRI) in space, starting 2017. Laser based metrology also includes optical clocks/references, either as ultra-stable light source for high sensitivity interferometry or as scientific payload e.g. proposed in fundamental physics missions such as mSTAR (mini SpaceTime Asymmetry Research), a mission dedicated to perform a Kennedy-Thorndike experiment on a satellite in a low-Earth orbit. To enable the use of existing optical laboratory setups, optimization with respect to power consumption, weight and dimensions is necessary. At the same time the thermal and structural stability must be increased. Over the last few years we investigated adhesive bonding of optical components to thermally highly stable glass ceramics as an easy-to-handle assembly integration technology. Several setups were implemented and tested for potential later use in space applications. We realized a heterodyne LISA related interferometer with demonstrated noise levels in the pm-range for translation measurement and nano-radiant-range for tilt measurements and two iodine frequency references on Elegant Breadboard (EBB) and Engineering Model (EM) level with frequency stabilities in the 10 -15 range for longer integration times. The EM setup was thermally cycled and vibration tested.